Body image perceptions and weight loss behavior among young adults - Ali Hanapiah, Nasuha Najwa; Sidek, Suriati (IIUM Press, 2018)
Introduction: University students tend to be more concerned on their body image and body shape concerns because of the surrounding The present study was conducted among undergraduate students at the International Islamic University Malaysia (IIUM) Kuantan with the aim to identify the body image perceptions, body shape concerns and weight loss behaviors. Methods: A total of 135 participants comprising of 50 male and 85 female undergraduate students were recruited from six Kulliyyah in IIUM Kuantan. The Contour Drawing Rating Scale, Body Shape Questionnaire (BSQ-16) and Weight Loss Behavior Scales (WLBS) were used as assessment tools. Results: The result showed 73.3% of students had normal BMI status, 6.7% were underweight and the remaining were overweight or obese. More than 50% of the participants were somewhat concern about their body shape. In addition, more than half of the participants (54.8%) were dissatisfied with their body image and had desired to be thinner. The most preferred weight loss behavior among the participants was exercise compared to other weight loss approaches. The result shows that concerns to dieting and weight have a significant association with BMI status. Meanwhile, body shape concerns are found to be significantly associated with concern to dieting and weight, as well as avoidance of fatty and sweet foods. However, there was no association between body shape concerns and exercise. Conclusion: Based on the findings, more tailored intervention programs that lead to healthy body image and weight loss behavior are needed among young adults.